Transition‐Metal‐Free Defluorosilylation of Fluoroalkenes with Silylboronates2. Issue 10 (6th September 2019) - Gao, Pan; Wang, Guoqiang; Xi, Longlong; Wang, Minyan; Li, Shuhua; Shi, Zhuangzhi
Summary of main observation and conclusion: Silylated fluoroalkenes are important synthetic intermediates with complementary reactivity, which play a key role in the construction of natural products, pharmaceuticals, and manmade materials. Converting the normally highly stable fluoroalkenes into silylated fluoroalkenes by selective defluorosilylation is a challenging task. Herein, we report a simple, inexpensive and robust defluorosilylation of a variety of fluoroalkenes with silylboronates in the presence of alkoxy base to directly synthesize various silylated fluoroalkenes. The protocol features mild and safe reaction conditions that avoid a catalyst, a transition metal, a ligand, and high reaction temperature and tolerates a wide scope of fluoroalkene substrates without compromising the efficiency. Density functional theory calculations show that transient silyl anion complex undergoes an SN 2' or SN V substitution, which is responsible for this base‐mediated defluorosilylation. Abstract : A mild, catalyst‐free system has been established for the defluorosilylation of various fluoroalkenes with silylboronates via C—F activation. This route employs an inexpensive alkoxy base and can be used to generate silylated fluoroalkenes with a variety of synthetically useful functional groups.